A production method for improving the structure and performance of titanium weld zone

By performing deformation heat treatment in the weld area of ​​the titanium cylinder sleeve, combined with manual tungsten argon arc welding and medium/high frequency induction heating, the problem of large differences between the weld structure and the base material is solved, and grain refinement and mechanical properties are achieved The improvement of the process flow simplifies and improves production efficiency.

CN115121917BActive Publication Date: 2024-12-24CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210889687.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2024-12-24
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

In the prior art, the weld structure of the titanium cylinder sleeve and the base material structure are too large, resulting in bright bands appearing in the production of electrolytic copper foils, affecting the quality and production efficiency of the copper foil. The traditional welding and heat treatment processes are complex and Inefficient.

Method used

By using deformation heat treatment method, heating and deformation are carried out simultaneously, through manual tungsten argon arc welding and medium/high frequency induction heating under rolling wheels, the weld area is 8 to 14% at a temperature of 500℃~650℃. Deform, simplify the process and refine the grains.

Benefits of technology

Effectively refine weld grains, reduce the difference between weld and base material structure, improve mechanical properties, reduce production costs and energy consumption, simplify process flow, and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115121917B_ABST
    Figure CN115121917B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of rare metal material modification, and specifically relates to a production method for improving the weld zone structure and performance of titanium materials. Imported TA1 titanium plates are selected as research objects, and the TA1 titanium plates are welded by manual tungsten inert gas arc welding. The weld of the titanium plate is subjected to thermomechanical treatment. Thus, a weld structure similar to the substrate structure is obtained. This method is beneficial to improving the weld zone structure and performance, and can effectively reduce the aspect ratio of the α phase and reduce the difference between the weld structure and the parent material structure. After thermomechanical treatment, the mechanical properties of TA1 can meet the requirements of national standards, and the peak hardness of the weld and the heat-affected zone decreases slightly with the increase of annealing temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare metal material modification, and in particular relates to a production method for improving the structure and performance of a titanium material weld zone. Background Art

[0002] Electrolytic copper foil is one of the basic materials for the manufacture of electronic products such as copper-clad laminates, printed circuit boards and lithium-ion batteries. The electrolytic method for producing copper foil is an efficient copper foil production method developed in recent years. The cathode roller is called the mother of electrolytic copper foil because copper ions are deposited on the surface of its roller cathode to generate electrolytic copper foil. At the same time, the roller rotates continuously in a circular motion, so that copper foil can be continuously generated and peeled off on it, and finally rolled into foil. It can be seen that copper foil is a continuation of the crystals on the surface of the cathode roller and a mirror image of its surface. The grains on the surface of the cathode roller are fine, and the copper foil crystals are fine. Conversely, the copper foil crystals are coarse. Therefore, in actual production, the microscopic geometric shape of the grains on the roller surface is required to be consistent, uniform in size, and orderly arranged.

[0003] At present, there are two main manufacturing processes for the manufacture of titanium sleeves on the surface of cathode rollers: spinning and welding. Among them, the seamless titanium cathode roller manufactured by the spinning process has the advantages of uniform surface grain size, no bright bands, color difference and other defects in the copper foil produced, and easy processing. Before spinning, the titanium cylinder ring blank must go through the process steps of "sponge titanium vacuum melting-ingot-punching-hole expansion-ring rolling-spinning". The process is relatively complicated, the material utilization rate is low (low yield rate), and more importantly, the processing fee of spinning itself is expensive. In addition, the spinning equipment and molds for manufacturing large-diameter sleeves are too expensive, forcing many companies to stop at this research and production.

[0004] The cathode roller produced by welding technology has the advantages of low cost, high production efficiency, and titanium sleeve manufacturing is not affected by diameter. However, due to the presence of a longitudinal weld on the surface of the cathode roller during the production process of this process, there is a bright band on the surface of the copper foil at the corresponding position in the production of electrolytic copper foil. If the welding and subsequent processing processes are not well controlled, there will be a light spot or bright band at the corresponding position of the (copper) foil, which seriously affects and restricts the high quality and high efficiency production of the copper foil. Correspondingly, there are also disadvantages such as difficulty in controlling the material properties of the weld area during the manufacturing process.

[0005] There are some studies in the prior art that heat treat the weld to reduce the difference between the weld structure and the base structure, thereby eliminating the periodic bright band printed on the foil by the weld structure. Among them, CN200410026157 is a method for manufacturing a titanium cathode roller body. The method mainly emphasizes heating the weld and the heat-affected zone first, cooling and protecting the base part, and then deforming the weld and heating it again. This process is relatively cumbersome and inefficient. CN200910213091.6 is a method for preparing a large titanium cathode roller. It is heated and recrystallized before deformation, that is, heated first and then deformed. As for the heating and pressing in the steps of this method, it means that the pressing and deformation are performed after the initial heating is completed. There will be problems such as large deformation resistance, easy defects, and deformation only occurs on the surface, and thick layer grains cannot be refined. Compared with the present invention, the steps of the welding method and the subsequent heat treatment method are relatively cumbersome, complicated to operate, and do not involve performance research such as mechanical properties and microhardness of each area of ​​the weld.

[0006] In order to solve the problem that the weld structure of the titanium sleeve produced by welding is too different from the parent material structure, most traditional processes use various treatment methods to refine the grains at the weld after welding. Some processes heat the weld first, then deform it, and then heat it again, and repeat this process many times; some processes deform the weld first and then heat it. In general, the two steps of deformation and heating are mechanically combined. Therefore, there are disadvantages such as complex process, cumbersome steps, and difficult operation. Summary of the invention

[0007] Based on the above technical problems, the present invention provides a production method for improving the structure and performance of the weld zone of titanium materials. The present invention combines deformation and heating, and heating and deformation are performed simultaneously, that is, deformation is performed while heating, which has the advantages of simplicity, low cost, and easy operation, and the final effect of grain refinement is good.

[0008] The technical solution adopted by the present invention to solve the technical problem is: a production method for improving the structure and performance of the weld zone of titanium material, comprising the following steps:

[0009] (1) Imported TA1 titanium plate was selected as the research object.

[0010] (2) The titanium plate is welded by manual tungsten inert gas welding;

[0011] The welding wire is made of the same material as the parent material, and the specific composition is shown in Table 1. The joint form adopts a single-sided 25° V-shaped groove with a blunt edge and a blunt edge height of 2mm, and multi-layer welding is performed. Pretreatment before welding: grind the test plate with a wire brush or a grinder, and clean it with alcohol or acetone to remove oil, dust, moisture, oxide film, etc. within 20mm on both sides of the weld; preheat the workpiece, preheat the test piece in a drying oven, and cool it to 50℃; positioning welding, positioning welding is performed after the alcohol is completely volatilized, and positioning welding is performed at both ends of the workpiece with a reserved weld gap, with a reserved gap of 3mm at the top and 2mm at the bottom, and a reverse deformation of 1.5°.

[0012] Table 1 Chemical composition of welding wire

[0013] wt.%

[0014] element C H N O Fe Ti content 0.011 0.0019 0.006 0.090 0.18 Balance

[0015] The specific welding parameters are: welding current 120-135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, number of layers 3-4, and the shielding gas is argon with a purity of 99.99%.

[0016] (3) The titanium plate after welding is subjected to thermal deformation treatment;

[0017] Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil and other dirt to ensure that there is no slag on the weld surface after deformation. The welded test plate is placed under the rolling wheel, with the weld placement direction parallel to the forward direction of the rolling wheel. The weld is heated to different test temperatures by a medium frequency sensor to perform deformation heat treatment on the weld.

[0018] The deformation heat treatment is as follows: the weld of the titanium plate is subjected to deformation heat treatment. The test only heats the weld and deforms the weld while heating. The weld area is heated by medium / high frequency induction heating. The equipment heating temperature can be adjusted in the range of 200-700℃ and the heating speed is 20℃·min -1 , deformation speed 3mm·s -1 , and the heating is terminated after reaching 500℃~650℃ and at the same time, the weld height after deformation is guaranteed to be ≤0.4mm (the deformation is 8~14%), and no heat preservation treatment or quenching is required, and natural cooling is sufficient.

[0019] Furthermore, the deformation amount is controlled to be 8-14%, and the best effect is obtained. Too large or too small will affect the microstructure of the weld and the degree of grain breakage in the weld area, thereby affecting the final grain refinement effect.

[0020] Furthermore, heating to a temperature of 500°C to 650°C is preferred. When the temperature is lower than 500°C, the effect of grain refinement is poor; when the temperature is higher than 650°C, the grains will grow and the effect is poor. The preferred conditions are: the heating temperature is 650°C and the deformation is 14%.

[0021] The deformation heat treatment of the present invention is to perform deformation at the same time as the heating begins. It is characterized by combining weld heat treatment and rolling together, which simplifies the production process, saves energy consumption and equipment investment, reduces the temperature difference from heating to rolling, is conducive to grain refinement, further improves its microstructure, reduces the difference between the weld structure and the parent material structure, and improves the mechanical properties.

[0022] Compared with traditional hot rolling which needs to be performed above the recrystallization temperature, the risk of grain growth caused by the heating process can be effectively avoided. In addition, the traditional method also requires vacuum annealing heat treatment, while the present invention does not require vacuum annealing heat treatment, which greatly shortens the process time and reduces energy consumption. It can also better refine the grains, improve their microstructure, and reduce the difference between the weld structure and the parent material structure.

[0023] (4) Sampling, testing and analysis of the titanium plate after thermomechanical treatment. The test analysis specifically includes:

[0024] 1) The cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0025] 2) Use HXD-1000TMC Vickers microhardness tester to perform hardness test and analysis;

[0026] 3) The American Instron 8802 electro-hydraulic servo mechanical testing machine was used to conduct relevant mechanical performance testing and analysis.

[0027] The inventive idea of ​​the present invention:

[0028] In order to make the structure of the weld closer to that of the parent material, the present invention performs deformation heat treatment on the titanium plate after welding. The deformation heat treatment can better refine the grains than the traditional deformation + heat treatment operations, and can obtain a sample with better comprehensive performance. The present invention combines heating and deformation at the same time, optimizes the process, reduces costs, and has made great progress in improving production efficiency compared to traditional processes.

[0029] The beneficial effects of the present invention are:

[0030] (1) The present invention adopts manual tungsten inert gas arc welding and optimizes the welding process, thereby avoiding the problem of excessive coarsening of grains at welding temperature and the formation of brittle and hard structures during the cooling process after welding.

[0031] (2) The present invention adopts a process of deformation heat treatment after welding, and deformation is carried out simultaneously during the heating process. Under the action of deformation pressure and temperature change, the grains can be more effectively refined, making them close to flakes in shape, and the performance of the weld is improved to a level that is basically consistent with that of the parent material. The effect is better than the conventional method of first deforming and then heat treating after welding, and the problem of grain growth during the heating process is avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The microstructure of the weld zone obtained in Example 1;

[0033] Figure 2 This is the microstructure of the weld zone obtained in Example 2;

[0034] Figure 3 is the microstructure of the weld zone obtained in Example 3;

[0035] Figure 4 The microstructure of the weld zone obtained in Example 4;

[0036] Figure 5 is the microstructure of the weld zone obtained in Example 5;

[0037] Figure 6 This is the microstructure of the weld zone obtained in Example 6;

[0038] Figure 7 This is the microstructure of the weld zone obtained in Example 7;

[0039] Figure 8 This is the microstructure of the weld zone obtained in Example 8;

[0040] Fig. 9 This is the microstructure of the weld zone obtained in Comparative Example 1;

[0041] Fig.10 This is the microstructure of the weld zone obtained in Comparative Example 2;

[0042] Fig.11 This is the microstructure of the weld area obtained in Example 3. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with the accompanying drawings. The present invention is further described below in conjunction with embodiments, but is not limited thereto.

[0044] The welding wire in the embodiment is made of the same material as the base material, with a diameter of Φ3mm and a specific composition of:

[0045] Chemical composition of welding wire

[0046] wt.%

[0047] element C H N O Fe Ti content 0.011 0.0019 0.006 0.090 0.18 Balance

[0048] The joint form adopts a single-sided 25° V-shaped groove with a blunt edge and a blunt edge height of 2mm for multi-layer welding. Pretreatment before welding: grind the test plate with a wire brush or a grinder, and clean it with alcohol or acetone to remove oil, dust, moisture, oxide film, etc. within a range of 20mm on both sides of the weld; preheat the workpiece, preheat the test piece in a drying oven, and cool it to 50℃; positioning welding, positioning welding is performed after the alcohol is completely volatilized, and positioning welding is performed at both ends of the workpiece with a reserved weld gap, with a reserved gap of 3mm at the top and 2mm at the bottom, and a reverse deformation of 1.5°.

[0049] Example 1

[0050] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0051] (2) The two titanium plates were welded by manual tungsten inert gas welding, with specific welding parameters: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas 99.99% argon;

[0052] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 500°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (the deformation amount is 8%);

[0053] (4) Samples were taken from the titanium plate after thermomechanical treatment and hardness test and analysis were performed using a HXD-1000TMC Vickers microhardness tester;

[0054] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0055] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0056] Example 2

[0057] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0058] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas was 99.99% argon;

[0059] (3) The titanium plate after welding was subjected to thermomechanical treatment. The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 550°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 10%);

[0060] (4) Samples were taken from the titanium plate after thermomechanical treatment and hardness test and analysis were performed using a HXD-1000TMC Vickers microhardness tester;

[0061] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0062] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0063] Example 3

[0064] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0065] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas was 99.99% argon;

[0066] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 600°C and the heating rate was 20°C min.-1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 12%);

[0067] (4) Samples were taken from the titanium plate after thermomechanical treatment and hardness test and analysis were performed using a HXD-1000TMC Vickers microhardness tester;

[0068] (5) Samples were taken from the titanium plate after thermomechanical treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0069] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0070] Example 4

[0071] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0072] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas was 99.99% argon;

[0073] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 650°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 14%);

[0074] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0075] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0076] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0077] Example 5

[0078] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0079] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 120A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 4 layers, and shielding gas was 99.99% argon;

[0080] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 500°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (the deformation amount is 8%);

[0081] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0082] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0083] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0084] Example 6

[0085] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0086] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 120A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 4 layers, and shielding gas was 99.99% argon;

[0087] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 550°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 10%);

[0088] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0089] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0090] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0091] Example 7

[0092] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0093] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 120A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 4 layers, and shielding gas was 99.99% argon;

[0094] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 600°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 12%);

[0095] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0096] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0097] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0098] Example 8

[0099] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0100] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 120A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 4 layers, and shielding gas was 99.99% argon;

[0101] (3) The titanium plate after welding was subjected to thermomechanical treatment. Before the test, the weld surface was ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there was no slag on the weld surface. The welded test plate was placed under the rolling wheel with the weld placement direction parallel to the forward direction of the rolling wheel. The heating target temperature of the medium frequency sensor was set to 650°C and the heating rate was 20°C min. -1 , while heating, the weld is deformed at a speed of 3mm﹒s -1 , the heating is terminated after reaching the set temperature and at the same time the weld height after deformation is ensured to be ≤0.4mm (deformation is 14%);

[0102] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0103] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0104] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0105] Comparative Example 1

[0106] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0107] (2) The two titanium plates were welded by manual tungsten inert gas welding, and the welding parameters were: welding current 120A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 4 layers, and shielding gas was 99.99% argon;

[0108] (3) Samples were taken from the titanium plate after welding and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0109] (4) Samples were taken from the titanium plate after welding, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0110] (5) According to the national standard GB / T3624-2010, samples were taken from the titanium plate after welding, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0111] Comparative Example 2

[0112] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0113] (2) The two titanium plates were welded by manual tungsten inert gas welding, with specific welding parameters: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas 99.99% argon;

[0114] (3) The titanium plate after welding is subjected to vacuum annealing treatment, and the annealing process is: temperature 500°C, holding time 2h;

[0115] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0116] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0117] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0118] Comparative Example 3

[0119] (1) Imported TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 85mm×37.5mm×8mm;

[0120] (2) The two titanium plates were welded by manual tungsten inert gas welding, with specific welding parameters: welding current 135A, welding speed 0.5cm / s, main nozzle 20L / min, support cover 12L / min, back side 10L / min, 3 layers, and shielding gas 99.99% argon;

[0121] (3) The titanium plate after welding is subjected to vacuum annealing treatment, and the annealing process is: temperature 650°C, holding time 2h;

[0122] (4) Samples were taken from the heat-treated titanium plate and hardness test and analysis was performed using a HXD-1000TMC Vickers microhardness tester;

[0123] (5) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope;

[0124] (6) According to the national standard GB / T3624-2010, samples were taken from the heat-treated titanium plates, and the relevant mechanical properties were tested and analyzed using an American Instron 8802 electro-hydraulic servo mechanical testing machine.

[0125] Table 2 Microhardness of each area of ​​the welded plate under different processes

[0126] Technology <![CDATA[Substrate (HV 0.10 )]]> <![CDATA[Heat Affected Zone (HV 0.10 )]]> <![CDATA[Weld zone (HV 0.10 )]]> Example 1 160 184 178 Example 2 158 180 176 Example 3 158 180 175 Example 4 158 176 172 Example 5 160 184 178 Example 6 158 182 176 Example 7 160 180 176 Example 8 160 175 173 Comparative Example 1 160 190 180 Comparative Example 2 161 188 181 Comparative Example 3 158 192 178

[0127] Table 2 shows the microhardness of different areas of the weld plate after heat treatment, and the hardness values ​​are the peak values ​​of each area. It can be seen from Table 2 that under the process conditions of Example 1, the microhardness of each area of ​​the weld plate is significantly reduced compared with the microhardness of each area of ​​Comparative Example 1 which is subjected to traditional annealing treatment. Excessive or small deformation affects the microhardness of each area, causing the microhardness of each area to increase slightly. And with the increase of temperature, the microhardness of each area has decreased significantly. It can be seen that deformation heat treatment of the sample after welding can effectively reduce the microhardness of each area of ​​the weld plate, and the effect will become more and more obvious with the increase of temperature.

[0128] Table 3 Mechanical properties of welded plates under different processes

[0129] Technology Tensile strength MPa Yield strength MPa Elongation % Substrate 259 153 45 Example 1 275 180 40 Example 2 273 178 38 Example 3 273 176 38 Example 4 270 175 35 Example 5 275 180 40 Example 6 274 178 39 Example 7 272 175 38 Example 8 270 175 36 Comparative Example 1 292 180 30 Comparative Example 2 290 182 31 Comparative Example 3 290 185 34

[0130] Table 4 National standards for mechanical properties of TA1

[0131]

[0132] Table 5 Grain grade of weld zone under different processes

[0133]

[0134]

[0135] Table 3 shows the mechanical properties corresponding to each stage. By comparing the mechanical properties of the welded plates under different process conditions, it can be seen that compared with the welded plates obtained by conventional production processes, after the deformation heat treatment, the tensile strength of the welded plates is reduced by 10-20MPa, the yield strength is reduced by 1-5MPa, and the elongation after fracture is increased by 5%-10%, and all meet the national standards. The closer to the mechanical properties of the substrate, the more it meets the process requirements. It can be seen that after this process treatment, the strength decreases and the elongation after fracture increases. The deformation heat treatment is conducive to improving the performance of the weld area, and the effect will become more and more obvious as the temperature increases.

[0136] The grain size of the weld just after welding is level 5, the grain size of the weld after traditional annealing is level 5.5, and the grain size of the weld after deformation heat treatment is level 7.5, while the grain size of the original parent material is about level 8, which is 0.5 level different from the grain size after deformation heat treatment. That is, deformation heat treatment can better refine the grains, improve its microstructure, and reduce the difference between the weld structure and the parent material structure.

[0137] from Figures 1 to 11 It can be found that the deformation heat treatment breaks the coarse columnar crystals of the weld by rolling, refines the weld grains, and improves the mechanical properties of the weld. Within a certain temperature range, as the temperature increases, the needle-shaped secondary α phase structure in the weld area is closer to the lamellar shape in morphology, which is closer to the parent material. And in the process of slow cooling from high temperature to room temperature, the β phase is transformed into fine grains of α phase or α+β phases, which further reduces the difference between the weld structure and the parent material structure. Post-deformation heat treatment has a significant effect on the structure of each area of ​​the weld. As the temperature increases, the structure of each area of ​​the weld is refined to a certain extent. Among them, 650℃ can effectively reduce the aspect ratio of the α phase, making it more similar to the parent material in morphology.

[0138] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A production method for improving the structure and performance of the titanium weld zone, characterized in that: The process steps of the method are as follows: (1) Select a titanium plate and a welding wire made of the same material as the titanium plate base material, and use manual tungsten inert gas arc welding for welding; (2) Thermomechanical treatment of the titanium plate after welding: The welded test plate is subjected to thermomechanical treatment, only the weld is heated, and the weld is rolled and deformed while heating. The weld area is heated by medium / high frequency induction heating, and the heating rate is 20℃·min -1 , deformation speed 3mm·s -1 ; When the weld is heated to 650℃ and the deformation of the weld is ensured to be 14%, the process is terminated. No insulation treatment or quenching is required, and it can be cooled naturally.

2. The production method for improving the structure and performance of the titanium material weld zone according to claim 1, characterized in that: The welding conditions of manual tungsten inert gas welding in step (1) are as follows: welding current 120-135A, welding speed 0.5cm / s, main nozzle 20L / min, support 12L / min, back 10L / min, number of layers 3-4, and shielding gas 99.99% argon.